Contribution of reservation through online and offline travel agents to increase room sales volume at New Kuta Hotel, Pecatu, Balii - Baiq Mega Yustika Kharomah; I Gede Mudana; Elvira Septevany (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This study aims to determine the reservation contribution of online and offline travel agent on room sales volume and the implication of the contribution towards New Kuta Hotel, Pecatu, Bali. Research methods: Analytical techniques of this study are classical assumption tests, multiple correlation analysis, multiple linear regression analysis, multiple determination analysis, and hypothesis tests (t-test and F-test) which are tested using SPSS program. Results and discussion: There are positive and significant contributions between Online Travel Agents and Offline Travel Agent to Room Sales Volume. Analysis of multiple determination test shows independent variables simultaneously contribute 99.4% to room sales volume, while 0.06% is influenced by other factors such as walk-in guest, MICE guest, and reservation through telephone. Conclusion: The ups and downs of the contribution of reservations through online and offline travel agents on the sales volume of New Kuta Hotel in the form of ups and downs hotel revenue, employee service charge and management opportunities to renovate the facilities of New Kuta Hotel, Pecatu, Bali.